Legal Presumption of Liability of the Vehicle Owner for Traffic Violations - Tičar, Bojan; Mesarič, Tine; Selišnik, Franjo (11. Nacionalna konferenca o varnosti v lokalnih skupnostih: Odpornost lokalnih skupnosti na varnostna tveganja, 2025)
In this article, we will draw attention to the open issue of the current regulation and practical implementation of the legal presumption from Article 8 of the Road Traffic Rules Act (»Zakon o pravilih cestnega prometa (ZPrCP)«, 2010), which is rigidly based on the constitutional privilege against self-incrimination. By establishing the presumption of responsibility of the owner or holder of the right to use a vehicle, the legislator tried to ensure that perpetrators of road traffic offences would actually be punished. Namely, the penal policy is one of the parts of the current regulation of the traffic system, which, taking into account the existing situation in road traffic, cannot be replaced equally effectively by other measures. Comparative legal solutions from Germany, Croatia, the Netherlands and Austria show that it is possible to introduce more effective models that respect the democratic and constitutional privilege against self-incrimination, and achieve the purpose of the law in cases where a road traffic offence was committed with a vehicle, but it is not possible to determine who the perpetrator is.